A supertree of temnospondyli: cladogenetic patterns in the most species-rich group of early tetrapods. - Ruta, M; Pisani, D; Lloyd, G; Benton, M (2007)
As the most diverse group of early tetrapods, temnospondyls provide a unique opportunity to investigate cladogenetic patterns among basal limbed vertebrates. We present five species-level supertrees for temnospondyls, built using a variety of methods. The standard MRP majority rule consensus including minority components shows slightly greater resolution than other supertrees, and its shape matches well several currently accepted hypotheses of higher-level phylogeny for temnospondyls as a whole. Also, its node support is higher than those of other supertrees (except the combined standard plus Purvis MRP supertree). We explore the distribution of significant as well as informative changes (shifts) in branch splitting employing the standard MRP supertree as a reference, and discuss the temporal distribution of changes in time-sliced, pruned trees derived from this supertree. Also, we analyse those shifts that are most relevant to the end-Permian mass extinction. For the Palaeozoic, shifts occur almost invariably along branches that connect major Palaeozoic groups. By contrast, shifts in the Mesozoic occur predominantly within major groups. Numerous shifts bracket narrowly the end-Permian extinction, indicating not only rapid recovery and extensive diversification of temnospondyls over a short time period after the extinction event (possibly less than half a million years), but also the role of intense cladogenesis in the late part of the Permian (although this was counteracted by numerous 'background' extinctions).